(Im)Mobilities in a postmigrant age: Narratives of forced migration in Jenny Erpenbeck's Go, Went, Gone and Elfriede Jelinek's Charges (The Supplicants). Issue 2 (1st October 2019) - Zimmermann, Sabine
Postmigrant conditions do not translate into easy access for migrants who arrive outside of the parameters of orderly migration. While European nations acknowledge the principle of asylum, massive efforts are made to prevent refugees from reaching the territory of the state where they could receive its protection. Even as their physical proximity to Europe increases, their legal proximity typically decreases. The novel Gehen, ging, gegangen (Go, Went, Gone) by German writer Jenny Erpenbeck depicts the experiences of non-privileged migrants whose tales of exile and displacement indicate that most of them will not be recognized as refugees. The play Die Schutzbefohlenen (Charges [The Supplicants]) by Austrian writer Elfriede Jelinek contrasts the treatment of asylum seekers with real-life cases of two 'VIP foreigners' who were granted naturalization by the Austrian government. Both texts convey a blunt message: The narratives of those who do (and those who do not) arrive in Europe's 'postmigrant societies' without legal status confirm that the gap between privileged and non-privileged migration is almost impossible to bridge.